Ferruginous coated grains of microbial origin from the Lower Devonian (Pragian) of the Prague Basin (Czech Republic) – Petrological and geochemical perspective - Vodrážková, Stanislava; Kumpan, Tomáš; Vodrážka, Radek; Frýda, Jiří; Čopjaková, Renata; Koubová, Magdalena; Munnecke, Axel; Kalvoda, Jiří; Holá, Markéta (Sedimentary Geology, 2022)
A unique occurrence of ironstone lenses represented by ferruginous oncoids is reported from the offshore Řeporyje Limestone (Lower Devonian, Pragian) from the Prague Basin (the Stydlé Vody Quarry). The oncoidal cortices show distinct arrangement of hematite/chamosite and/or iron-bearing calcite laminae, which are irregular, wavy and with a relatively high degree of inheritance of shape of the topography of the underlying laminae. Micro-domes and bulges, comparable to those observed in stromatolites and laminae overgrowing topographic irregularities represented by agglutinated foraminifers cemented to oncoid surfaces, were fairly commonly observed. The foraminifers probably represent the earliest representatives of agglutinated foraminifera encrusting surfaces of ferruginous grains. The surfaces of oncoids are wavy and often wrinkled. Although no microbial remains that could have been directly associated with oncoidal growth were recorded, we regard above mentioned features as indicators of biogenicity of the precipitates. We could only speculate the nature of the microbial consortia, but we regard the alternation of Fe2+ (chamosite, iron-bearing calcite) and Fe3+ (hematite) phases as a result of coupled oxidation - reduction processes related to passive and/or active microbial metabolic activities (precipitation of ferrihydrite – hematite precursor) and passive mineral authigenesis mediated by microorganisms (precipitation of chamosite precursor). Spatially restricted occurrence of the oncoidal lenses along with Al/Al + Fe + Mn vs. Fe/Ti, Nd vs. Ce/Ce*, Eu/Sm vs. Sm/Yb and other crossplots suggest that hydrothermal fluids were the most probable source of ferrous iron. Since most of the known oolitic or oncolitic ironstones represent rather large sedimentary bodies deposited around storm wave base to shallow subtidal environments under influence of upwelled anoxic watermasses or continental runoff, the reported oncolitic mounds represent a specific example of ironstones formation.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Ironstones; Microbialites; Oncoids; REE geochemistry; Trace elements geochemistry